2019
DOI: 10.3390/molecules24203722
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Donor DETA/NO Inhibits the Growth of Endometrial Cancer Cells by Upregulating the Expression of RASSF1 and CDKN1A

Abstract: Nitric oxide (NO) is implicated in several biological processes, including cancer progression. At low concentrations, it promotes cell survival and tumor progression, and at high concentrations it causes apoptosis and cell death. Until now, the impact of NO donors has not been investigated on human endometrial tumors. Four cancer cell lines were exposed to different concentrations of DETA/NO for 24 to 120 h. The effects of DETA/NO on cell proliferation and invasion were determined utilizing MTS and Boyden cham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…These cells in their functional state also produce increased levels of TNFα and iNOS, which contribute to the killing of tumor cells. Nitric oxide production is associated with decreased cancer progression, metastasis and differentiation [ 30 , 31 , 48 ]; however, its role in OVCA chemoresistance is less explored. We demonstrated that M1 macrophage-derived, NO-sensitized, chemoresistant OVCA cell to CDDP-induced death by upregulating ROS production and reducing GSH synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells in their functional state also produce increased levels of TNFα and iNOS, which contribute to the killing of tumor cells. Nitric oxide production is associated with decreased cancer progression, metastasis and differentiation [ 30 , 31 , 48 ]; however, its role in OVCA chemoresistance is less explored. We demonstrated that M1 macrophage-derived, NO-sensitized, chemoresistant OVCA cell to CDDP-induced death by upregulating ROS production and reducing GSH synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with other reports that have shown iNOS expression in OVCA as a favorable prognostic indicator of disease-related survival [ 30 ]. In other reports, nitric oxide donors have been shown to induce cancer cell death by upregulating the expression of RASSF1 and CDKN1A [ 48 ], activating caspase 8/3 [ 49 ] and regulating anti-apoptotic BCL-2 family members [ 50 ]. Whether NO-induced ROS accumulation results in the activation of other pro-apoptotic genes requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, b-Gal NONOate is a promising prodrug for targeting intracellular NO, which is expected to become a potential therapeutic drug for cancer ETA/NO dose-and time-dependently induced the cell viability of human endometrial tumors. The mechanism is activating caspase-3 and arresting cell cycle at the G0/G1 phase, associated with attenuating the expression of cyclin-D1 and D3 (Waheed et al, 2019).…”
Section: Inhibition Of Tumor Growth Invasiveness and Angiogenesismentioning
confidence: 99%
“…The molecular mechanisms of development of EC are not fully understood. Although many oncogenes and tumor suppressors have been identified as key players underlying tumorigenesis of EC ( 4 - 6 ), however, almost no commonly-accepted biomarkers have been established to facilitate the comprehensive management of EC patients. Therefore, understanding the molecular events underlying endometrial carcinogenesis and identifying new biomarkers and therapeutic targets will be important.…”
Section: Introductionmentioning
confidence: 99%